Development of a sensitive enzyme immunoassay (ELISA) for specific identification of Lachesis acrochorda venom (2012)
ABSTRACT: The snake genus Lachesis provokes 2 to 3% of snakebites in Colombia every year. Two Lachesis species, L. acrochorda and L. muta, share habitats with snakes from another genus, namely Bothrops asper and B. atrox. Lachesis venom causes systemic and local effects such as swelling, hemorrhaging, myonecrosis, hemostatic disorders and nephrotoxic symptoms similar to those induced by Bothrops, Portidium and Bothriechis bites. Bothrops antivenoms neutralize a variety of Lachesis venom toxins. However, these products are unable to avoid coagulation problems provoked by Lachesis snakebites. Thus, it is important to ascertain whether the envenomation was caused by a Bothrops or Lachesis snake. The present study found enzyme linked immunosorbent assay (ELISA) efficient for detecting Lachesis acrochorda venom in a concentration range of 3.9 to 1000 ng/mL, which did not show a cross-reaction with Bothrops, Portidium, Botriechis and Crotalus venoms. Furthermore, one fraction of L. acrochorda venom that did not show crossreactivity with B. asper venom was isolated using the same ELISA antibodies; some of its proteins were identified including one Gal-specific lectin and one metalloproteinase. This test may be useful to physicians, since it could be applicable for tracking the kinetic distribution of antigens in patients or experimentally envenomed animals.